NATIVE AND NONNATIVE PROCESSING OF ACTIVE AND PASSIVE SENTENCES: THE EFFECTS OF PROCESSING INSTRUCTION ON THE ALLOCATION OF VISUAL ATTENTION. Issue 4 (September 2019) - Lee, James F.; Doherty, Stephen
Abstract: The present study compares native and nonnative processing of Spanish active and passive sentences. The nonnative speakers were tested before and after receiving processing instruction on the Spanish passive. The native speakers were tested once and provide a baseline for comparisons. We measured accuracy and response time to select the correct response in a paired picture matching task. We used eye-tracking measures to capture processing behaviors on both active and passive verb forms. We measured processing using time to first fixation on the verb area of interest, mean first fixation duration, mean first pass time, and mean second pass time. The results revealed that processing passive sentences comes at a cost to both native and nonnative speakers. After instruction the nonnative speakers showed no significant differences with native speakers in accuracy and response time. Also, the nonnative speakers' processing behaviors became more nativelike but did not reach the native speaker level.